Clinical Evaluation of Amrutatadi Yoga and Amruta-Nagaradi Kwath in the Management of Vata Rakta w.s.r to Gouty Arthritis - Raina, Namartha; sharma, Rajesh; Bibi, Rukshana (International Research Journal of Ayurveda & Yoga, 2021)
Vatarakta is more distressing and common metabolic disorder prevalent in present era .It is characterized by severe pain ,tenderness ,inflammation and burning sensation in the affected joints. It is a vata pradhana tridoshaja vyadhi where is main dushya . Sedentary life style along with mental stress, consumption of non -vegetarian and highly protein diet ,excessive alcohol are some of the precipitating factors which cause acute exacerbation of vatarakta. The aetiological factors responsible for gouty arthritis ,pathology and clinical features are quite similar with the vatarakta .Gouty arthritis is a complex metabolic disorder of protein , which results from deposition of monosodium monohydrate urate crystals in joint space or periarticular tissues causing inflammatory arthritis .It is more common in man after adolescence or in women after menopause .In modern science number of drugs available for management of gout but all of the drugs is associated with adverse effects and certain limitations.